Perspektif Hukum Mengenai Kasus Rahasia Dagang Antara Indomie Dan Mie Gaga Dilihat Dari Hukum Kekayaan Intelektual - Niken Aulia Kusumawati; Yukova Miska Athira; Mustaqim Mustaqim (Universitas Sains dan Teknologi Komputer, 2024)
In this era of globalization, intellectual property plays an important role in driving innovation and commercial competition. Trade secrets are an important element in this situation that requires legal protection. The purpose of this research is to examine the legal aspects of trade secret issues involving two well-known instant noodle companies, Indomie and Mie Gaga, with an emphasis on Indonesian intellectual property law. The food sector has developed rapidly and is ingrained in people's daily lives, especially with regard to instant noodles. One of the industry leaders, Indomie, has developed exclusive recipes and production techniques. The legal troubles over Gaga Noodles, a fast-growing new brand, show how difficult it is to legally protect trade secrets. This research is important because it adds to our knowledge about the Indonesian legal system's handling of trade secret issues, especially in the country's dynamic food sector. Through an examination of legal viewpoints, this research will offer a valuable perspective for the creation of relevant regulations, corporate procedures, and guidelines. It is hoped that this research will increase the protection of innovation and creativity in the business sector by providing a deeper understanding of the legal perspective surrounding the trade secret case between Indomie and Mie Gaga. This will help shape Indonesia's legal framework for intellectual property. With an emphasis on elements of intellectual property law, this research attempts to examine a court case involving trade secret claims between two well-known companies, Indomie and Mie Gaga. A comparative review of the legal protection for trade secrets under the Indonesian Intellectual Property Law is part of this research. This research approach includes a thorough case study of relevant legal and judicial developments, and a thorough analysis of the data collected to understand the fundamental ideas and applications of law relating to trade secrets in Indonesia. It is hoped that the findings of this research will provide a comprehensive understanding of how trade secret disputes in the food business sector are handled under intellectual property law. The real world impact of